2015
DOI: 10.1007/s11262-015-1234-5
|View full text |Cite
|
Sign up to set email alerts
|

Putative phage-display epitopes of the porcine epidemic diarrhea virus S1 protein and their anti-viral activity

Abstract: Porcine epidemic diarrhea virus (PEDV) is a pathogen of swine that causes severe diarrhea and dehydration resulting in substantial morbidity and mortality in newborn piglets. Phage display is a technique with wide application, in particular, the identification of key antigen epitopes for the development of therapeutic and diagnostic reagents and vaccines. To identify antigen epitopes with specificity for PEDV, a monoclonal antibody (MAb-5E12) against the immunodominant region of the PEDV Spike protein (S1) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…In addition, the relocalization of occludin upon PEDV infection is also seen in noninfected cells, suggesting indirect effects of PEDV on the cellular distribution of occludin. Since others have reported that PEDV-infected Vero E6 and IPEC-J2 cells do not produce type I interferon (38,39), we infer that the internalization of occludin in noninfected cells may be induced by some other pathophysiologic stimuli, such as proinflammatory cytokines (40). Jung and colleagues demonstrated that PEDV infection resulted in structurally altered tight junction proteins ZO-1 and E-cadherin in the villous epithelium in vivo (41).…”
Section: Discussionmentioning
confidence: 83%
“…In addition, the relocalization of occludin upon PEDV infection is also seen in noninfected cells, suggesting indirect effects of PEDV on the cellular distribution of occludin. Since others have reported that PEDV-infected Vero E6 and IPEC-J2 cells do not produce type I interferon (38,39), we infer that the internalization of occludin in noninfected cells may be induced by some other pathophysiologic stimuli, such as proinflammatory cytokines (40). Jung and colleagues demonstrated that PEDV infection resulted in structurally altered tight junction proteins ZO-1 and E-cadherin in the villous epithelium in vivo (41).…”
Section: Discussionmentioning
confidence: 83%
“…Three different groups of S1 proteins from co‐viral infections shared less than 12% amino acid sequence identities with each other (Wang, Deng et al., ). The B‐cell response is directed against the spike protein of coronaviruses (Cao et al., ) and it plays an important role in pathogenesis of virus infection.…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA was extracted using RNA extraction kit (Qiagen, Germany), and cDNA was synthesized by using cDNA reverse transcription kit (ThermoFisher, USA) with oligo dt primer. The cDNA was then subjected to real-time PCR with primer pairs specific for PEDV and βactin (Cao et al 2015). The β-actin gene served as the endogenous control.…”
Section: Qds-605 Labeled Sdab-mc37 As Probes Imaging Pedv In Vero Cellsmentioning
confidence: 99%